(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Obsessive-compulsive disorder (OCD) is a neuropsychiatric condition characterized by persistent and distressing obsessions and compulsions. These repetitive behaviors or thoughts often lead to significant distress and interference in daily life. Among the most common obsessional themes is an intense preoccupation with contamination and illness. The objective of the study is to determine frequency of obsessive compulsive disorder in medical students. Material and Methods: After approval of the study proposal from Ethical review Board of college of physician and surgeon Pakistan a cross sectional study was conducted in the Department of Psychiatry, Allama Iqbal Medical College / Jinnah Hospital, Lahore. over a period of six months from 17-05-2022 to 17-11-2022. Detailed history was taken to assess for exclusion criteria. To assess for presence of obsessive compulsive disorder (OCD) all the medical students included in study was asked a series of questions using Yale-Brown Obsessive This was followed up by a one on one interview of these students with a consultant psychiatrist to make as well as re-affirm the diagnosis. Results: We found that total of 140 students, 51.4 %( n=72) were in age group of 17-22 years and 48.6 %( n=68) were in age group of 23-28 years, mean age was 22.34±1.79 years and BOC scale was 5.40±8.78. There were 40.7 %( n=57) male and 59.3% (n=83) females. According to severity of symptoms, 77.9% (n=109) had subclinical, 2.9% (n=4) mild, 11.4% (n=16) moderate, 5.7% (n=8) severe and 2.1% (n=3) had extreme symptoms. Frequency of OCD was 22.1 % (n=31). There was significant association of age and gender with OCD (P-value<0.05) Conclusion: The results clearly show the impact of being a medical student and the need to increase awareness of obsessive compulsive disorder (OCD) among health workers generally and medical students specifically.